2006
DOI: 10.1111/j.1471-4159.2006.04199.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that quinolinic acid severely impairs energy metabolism through activation of NMDA receptors in striatum from developing rats

Abstract: In the present study we investigated the effect of intrastriatal administration of 150 nmol quinolinic acid to young rats on critical enzyme activities of energy production and transfer, as well as on 14 CO 2 production from [1-14 C]acetate at distinct periods after quinolinic acid injection. We observed that quinolinic acid injection significantly inhibited complexes II (50%), III (46%) and II-III (35%), as well as creatine kinase (27%), but not the activities of complexes I and IV and citrate synthase in str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 93 publications
(193 reference statements)
1
23
0
Order By: Relevance
“…Here, we explored the relevance of trp catabolism in malignant gliomas beyond immunoactive metabolites and addressed the relevance of quinolinic acid for stress resistance. Quinolinic acid has previously mainly been studied as a neurotoxin accumulating in the CNS of patients with neurodegenerative diseases where it causes excitotoxicity by binding and activating the NMDA receptor (44)(45)(46)(47). Its physiologic relevance as a NAD þ precursor has received much less attention possibly because it has been viewed as a less relevant NAD þ synthesis pathway compared with the de novo NAD þ synthesis pathway through NAMPT or the NAD þ -recycling pathway through NAPRT.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we explored the relevance of trp catabolism in malignant gliomas beyond immunoactive metabolites and addressed the relevance of quinolinic acid for stress resistance. Quinolinic acid has previously mainly been studied as a neurotoxin accumulating in the CNS of patients with neurodegenerative diseases where it causes excitotoxicity by binding and activating the NMDA receptor (44)(45)(46)(47). Its physiologic relevance as a NAD þ precursor has received much less attention possibly because it has been viewed as a less relevant NAD þ synthesis pathway compared with the de novo NAD þ synthesis pathway through NAMPT or the NAD þ -recycling pathway through NAPRT.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of all cytokines in pregnant women (Tsunoda et al 2003) or, generalising, at least the inflammatory cytokines (Zhang et al 2008) may 1 The potential toxicity may result from the agonism of the 3HK metabolite quinolinic acid at NMDA receptors (Ribeiro et al 2006). But, it may be noted that further metabolism to NAD(?)…”
Section: Smokingmentioning
confidence: 98%
“…Supporting the previous studies, intrastriatal QA injection significantly impaired mitochondrial enzyme activities in the striatum (Ribeiro et al, 2006). Further, report indicated that mitochondrial complex inhibitors preferentially damage substantia nigra dopamine neurons in rat brain slices (Bywood and Johnson, 2003).…”
Section: Discussionmentioning
confidence: 66%